The Remittance and the Private Investment in Nepal - Didiya, Muraj (Bagiswori Journal, 2019)
The paper aims to analyze the relationship between remittance and private investment in Nepalese economy. The study used the Least Squared Regression Analysis with 43 years' time series data of remittance inflow and private investment over the period of FY 1974/75 to 2017/18 of Nepal. The study found that foreign remittance has a significant positive impact on private investment of Nepalese economy.